Isolator-Free Unidirectional Multiwavelength Tm-Doped Double-Clad Fiber Laser Based on Multimode Interference Effect - Meng Wang; Junqing Zhao; Yijian Huang; Shenghua Lin; Shuangchen Ruan (IEEE Photonics Journal)
In this paper, an isolator-free unidirectional multiwavelength Tm-doped fiber laser is experimentally investigated. The isolator-free unidirectional operation of the laser is realized by the construction of a type of theta cavity. A single-mode-multimode-single-mode fiber structure served as a multimode interference filter is employed for implementing multiwavelength operation. Wavelength numbers from one to three can be obtained by increasing the pump power and properly adjusting the polarization controller. Besides the single wavelength emission at ∼2002.6 nm, dual-wavelength operations (∼1952.6 nm, ∼1954.7 and ∼1954.8 nm, ∼2002.7 nm) with signal-to-noise ratios larger than ∼46 dB and three-wavelength operation (∼1952.8, ∼1954.5, and ∼2002.9 nm) with signal-to-noise ratios larger than ∼50 dB have also been obtained, respectively. The maximum output power of ∼545 mW was obtained at pump power of ∼7.3 W, when the laser operates at three-wavelength oscillation and the slope efficiency is ∼10%. Our demonstrated fiber laser source represents a type of all-fiberized solution for the realization of high-power, unidirectional and controllable multiwavelength operations, simultaneously.